The Case Study of Islamic-Education Leadership Model: What We Can Learn from the Dynamics of Principals’ Leadership in Indonesian Excellence Islamic Boarding-Schools - Erika Setyanti kusumaputri; Hanifah Latif Muslimah; Enny Iroh Hayati (Jurnal Psikologi, 2023)
Educational leadership research has been more oriented toward western theories and contexts, ignoring the contextual conditions that shape leadership styles and characteristics. Whereas some ideas analyze that leadership is inseparable from context and is more appropriate according to the setting of a particular society. This study aims to avoid bias when interpreting leadership patterns by finding a concept of Islamic leadership in the field of Education. This research was conducted using qualitative research methods with a case study approach. The participants of the study were two principals and five academic staff in two well-known excellent Islamic senior high schools which become school models pointed out by MORA Indonesia. The data validity checking technique was done by credibility test including method triangulation namely using direct interviews, observations, online surveys, and data sources triangulation using participative observations, school archives, field notes, photos, and video documentation while the researchers were at the location. Triangulation is used to check data from various sources in various ways. Study results showed that the principal's leadership pattern implemented Islamic religious values and the context of the society. Indonesia is predominantly Muslim, where Islamic-based education has been facilitated by the state and included in the policy system, so the findings can be considered when carrying out educational management based on Islamic values.